THE WAYANG AND ITS ENCHANTING LITTLE PUPPETEERS: EXPLORING COGNITIVE ABILITIES OF CEREBRAL PALSY CHILDREN THROUGH PERFORMANCE - Mumtaz Begum Aboo Backer; Pravina Manoharan, (Jurnal Gendang Alam (GA), 2022)
Wayang Kulit or shadow theatre, an ancient theatrical performance practice has given opportunity and space for researchers to explore the possibilities of creating a stimulating environment for performance and cognitive development among cerebral palsy children. This study looks at how three important performative elements in Wayang Kulit performance, “story-telling, role-playing and space” are explored for the development of cognitive abilities; i) to learn, ii) to sequence and iii) to reason, among cerebral palsy children. The study employs an action-research methodology which looks at participation-observation and artistic processes ranging from drama/theatre approaches to speech and vocal exercises. To assist the children in achieving the intended goals, “sensitive assistance” approach was also employed whereby teachers/facilitators assist the children during the workshop and training sessions. The cerebral palsy children were not only the participants of the workshops but more importantly, were the performers, storytellers, musicians, and puppeteers. Findings of this study show the children could, a) memorize the script (ability to learn), b) present the script in a story-telling manner (ability to sequence), c) role-play (to reason), and d) understand the mechanism of the performative setting (on and off stage). In addition, the study shows that through the sessions conducted via Wayang Kulit performance, the children learned to communicate, respond to each other, and also express themselves emotionally.